Update culture and the afterlife of digital writing - Gallagher, John R., author; Utah State University Press, publisher (Colorado State University. Libraries, 2019)
Explores "neglected circulatory writing processes" to understand why and how digital writers compose, revise, and deliver arguments that undergo (sometimes constant) revision. Also looks at how digital writers respond to comments, develop a brand, and evolve their arguments-all post-publication.--Provided by publisher.
Methods and participants -- Template rhetoric -- Textual timing -- Textual attention -- Textual management -- Ethics in update culture -- Learning and pedagogy in update culture -- An epistemology of change.
Keywords: Electronic publishing; Authors and publishers